Keadilan Anak Perspektif Undang-Undang No.11 Tahun 2012 tentang Sistem Peradilan Anak: Menilik Strategi Implementasi Diversi Di Kepolisian Dan Pengadilan Negeri Kota Metro Dalam Mewujudkan Keadilan Restroaktif - Murdiana, Elfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
Being introduced the concept of diversion arranged in constitution of child criminal justice system 2012 gives the different nuance for the implementation of child criminal justice system in Indonesia. Therefore, the implementation of diversion concept becomes a definiteness that must be noticed. In realizing the retroactive justice for children, the implementation of law becomes one of the important components. Thus, it is need to be understood the strategy of implementation carried out by the upholder as the law structure. This is a library research by using documentation as the data collection technique. The result of the research shows that the preparation of facilities and infrastructure in handling the diversion problem for children is one of the implementation strategies done by the state court of Metro. Whereas, the investigation in police resort of Metro has not had special space used, so that it can be one of the constraint faced by the institution of diversion implementer if considered from the culture aspect.